Screening, molecular identification, population diversity, and antibiotic susceptibility pattern of Actinomycetes species isolated from meat and meat products of slaughterhouses, restaurants, and meat stores of a developing country, Iran - Motallebirad, Tahereh; Mardanshah, Omid; Safarabadi, Mehdi; Ghaffari, Kazem; Orouji, Mohammad Ali; Abedi, Behnam; Azadi, Davood (Frontiers in Microbiology, 2023)
Actinomycetes can colonize surfaces of tools and equipment and can be transferred to meat and ‎meat products during manufacture, processing, handling, and storage. Moreover, washing the meat ‎does not eliminate the microorganisms; it only spreads them. As a result, these opportunistic ‎pathogens can enter the human body and cause various infections. Therefore, the aim of the ‎current study was to screen, identify, and determine the antibiotic susceptibility of Actinomycetes ‎species from meat and meat products in the Markazi province of Iran.A total of 60 meat and meat ‎product samples, including minced meat, mutton, beef, chicken, hamburgers, and sausages, were ‎collected from slaughterhouses, butchers, and restaurants in the Markazi province of Iran. The ‎samples were analyzed using standard microbiological protocols for the isolation and ‎characterization of Actinomycetes. PCR amplification of hsp65 and 16SrRNA genes and sequence ‎analysis of 16SrRNA were used for genus and species identification. The minimum inhibitory ‎concentrations (MICs) of antimicrobial agents were determined by broth microdilution ‎method and interpreted according to the CLSI guidelines.A total of 21(35%) Actinomycetes ‎isolates from 5 genera and 12 species were isolated from 60 samples. The most prevalent ‎Actinomycetes were from the genus Mycobacterium, with 6(28.6%) isolates (M. avium complex, ‎M. terrae, M. smegmatis, and M. novocastrense), followed by the genus Rhodococcus with 5 ‎‎(23.8%) isolates (R. equi and R. erythropolis), the genus Actinomyces with 4(19.1%) isolates (A. ‎ruminicola and A. viscosus), the genus Nocardia with 4(19.1%) isolates (N. asiatica, N. seriolae, ‎and N. niigatensis), and the genus Streptomyces with 2(9.5%) isolates (S. albus). Chicken and ‎sausage samples had the highest and lowest levels of contamination, respectively, with 6 and 1 ‎isolates. The results of drug susceptibility testing (DST) showed that all isolates were susceptible to ‎Ofloxacin, Amikacin, Ciprofloxacin, and Levofloxacin, whereas all of them were resistant to ‎Doxycycline and Rifampicin. The findings suggest that meat and meat products play an important ‎role as a reservoir for the transmission of Actinomycetes to humans, thus causing life-threatening ‎foodborne diseases such as gastrointestinal and cutaneous disorders. Therefore, it is essential to ‎incorporate basic hygiene measures into the cycle of meat production to ensure food safety.‎